POLICING TRANSFORMATION IN THE CRYPTO ERA IN HANDLING TOKEN-BASED MONEY LAUNDERING IN INDONESIA - Indah Hartantiningrum; Eva Achjani Zulfa; Chairul M. Setyabudi; M. Syaroni Rofii (RADJA PUBLIKA, 2025)
The purpose of this study is to analyze how policing transformation in Indonesia can be carried out to address token-based money laundering, as well as to provide policy recommendations that can improve the effectiveness of law enforcement in the context of the development of crypto technology. Adopting a post-positivism paradigm and a qualitative approach to explore policing transformation in handling token-based money laundering in Indonesia. The data collected will be analyzed using qualitative analysis techniques, including coding and thematic analysis, to find relevant main patterns and themes. The results of the study indicate that the main challenges in law enforcement against crypto-based money laundering in Indonesia include a lack of insight into blockchain technology and cryptocurrency, inadequate policies, and difficulties in tracking transactions due to the decentralized nature and anonymity of digital assets. To overcome this problem, it is necessary to increase the technological capacity of law enforcement officers, develop special trained units, and implement stricter regulations. In addition, community empowerment through education and training for police officers is very important to improve competence in detecting suspicious transactions. With these strategic steps, it is hoped that cyber security can be more assured and the digital asset ecosystem in Indonesia will become more transparent and responsible.